Outlining Strategies for Increasing Health Accessibility in Rural Areas of Indonesia - Nora Lelyana (Westscience Press, 2024)
This study examines strategies for increasing health accessibility in rural areas of Indonesia by addressing the multifaceted challenges faced by rural communities. The study looks at the main things that make healthcare hard to get, such as socioeconomic factors, cultural beliefs, geographical limitations, and flaws in the current healthcare delivery systems. It does this using qualitative research methods and secondary data. Through a comprehensive review of existing literature and data sources, the study identifies key barriers to healthcare access and explores opportunities for promoting health equity in rural Indonesia. Findings reveal that poverty, transportation barriers, traditional healing practices, and geographic isolation significantly hinder health accessibility in rural communities. Furthermore, weaknesses within the healthcare system, such as limited resources and fragmentation, exacerbate disparities in access to quality care. However, the study also highlights opportunities for leveraging community engagement, technology, and public-private partnerships to overcome these challenges and enhance healthcare delivery in rural Indonesia. By addressing these barriers and capitalizing on available resources, policymakers can develop tailored strategies to improve health accessibility and promote equitable healthcare outcomes in rural areas. Keywords: community engagement, health accessibility, public-private partnerships, rural areas